Out of Practice : Fighting for Primary Care Medicine in America - Barken, Frederick M. (Frederick Mitchell), 1955- (Book collections on Project MUSE., 2011)
The author uses his own experiences as a primary care physician to describe the state of his profession and argues that the health care system will collapse without a strong physician-patient relationship and that the role of the primary care physician must change to survive.